2020
DOI: 10.18502/ijph.v48i9.3013
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lung Cancer and Tea-Drinking Habits of Different Subgroup Populations: Meta-Analysis of Case-Control Studies and Cohort Studies

Abstract: Background: We aimed to investigate the association between lung cancer and tea-drinking habits of different subgroup populations. Methods: Systematic search of the PubMed, Web of Science, China National Knowledge Infrastructure (CNKI) and Sinomed databases from database construction until January 2017 for English and Chinese language articles on association of lung cancer and tea drinking. Meta-analysis was used to calculate the combined odds ratio (OR) value and its 95% confidence interval (95% CI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Among reproductive organ-related cancers, meta-analyses on endometrial cancer [78] and ovarian cancer reported inverse associations RR = 0.89 (95% CI 0.84-0.94) and RR = 0.64 (95% CI 0.45-0.90), respectively [76]. An inverse association was also found for lung cancer OR = 0.69 (95% CI 0.48-0.82) [58], non-Hodgkins lymphoma RR = 0.61 (95% CI 0.38-0.99) [62] and oral cancer RR = 0.85 (95% CI 0.75-0.93) [64].…”
Section: Cancermentioning
confidence: 97%
See 2 more Smart Citations
“…Among reproductive organ-related cancers, meta-analyses on endometrial cancer [78] and ovarian cancer reported inverse associations RR = 0.89 (95% CI 0.84-0.94) and RR = 0.64 (95% CI 0.45-0.90), respectively [76]. An inverse association was also found for lung cancer OR = 0.69 (95% CI 0.48-0.82) [58], non-Hodgkins lymphoma RR = 0.61 (95% CI 0.38-0.99) [62] and oral cancer RR = 0.85 (95% CI 0.75-0.93) [64].…”
Section: Cancermentioning
confidence: 97%
“…Table 2 reports results from meta-analyses on green tea and cardiovascular-related outcomes [14,21,22,[84][85][86][87]. Three 2 [13,14,22,26,34,40,45,54,58,62,64,65,69,76,78]. Note: Colorectal, lung and pancreatic cancer risk reported as Odds Ratios.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive review by Abe and Inoue [60] showed that most meta-analyses found inverse associations between green tea consumption and endometrial cancer (RR = 0.89; 95% CI = 0.84-0.94) [61], lung cancer (OR = 0.69; 95% CI = 0.48-0.82) [62], non-Hodgkin's lymphoma (RR = 0.61; 95% CI = 0.38-0.99) [63], oral cancer (RR = 0.85; 95% CI = 0.78-0.93) [64], and ovarian cancer (RR = 0.64; 95% CI = 0.45-0.90) [65]. Meanwhile, mixed results were observed in breast, esophageal, gastric, and hepatic cancers.…”
Section: Epidemiological Studies On the Anticancer Effects Of Green Teamentioning
confidence: 99%
“…However, the study design (case-control or cohort) and the sex of the participants can affect the strength of the association between tea consumption and lung cancer risk. In a most recently published meta-analysis ( 11 ), tea consumption was proven to be associated with decreased lung cancer risk (odds ratio 0.80; 95% CI: 0.73–0.87). Consumption of 7.5 g of green tea a day can significantly decrease lung cancer risk, as demonstrated by both case-control studies and cohort studies.…”
Section: Overview Of Findingsmentioning
confidence: 99%